ANALISIS PENERAPAN DEEP LEARNING PADA MATERI MERAWAT KEUTUHAN BANGSA DAN NEGARA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS VIII FASE D8 DI SMP NEGERI 17 KOTA JAMBI - Diva, Cintya; Melisa; Ichsan, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pancasila Education plays a strategic role in developing students' character, national awareness, and the ability to implement Pancasila values in daily life. The current educational paradigm encourages learning approaches that promote meaningful understanding, critical thinking, and active student participation. One of the approaches introduced is Deep Learning, which emphasizes meaningful, mindful, and joyful learning This study aims to analyze the implementation of the Deep Learning approach in the topic of Maintaining National Unity in Grade VIII Pancasila Education at SMP Negeri 17 Jambi City and to examine its impact on students' understanding of Pancasila values. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving Pancasila Education teachers, the vice principal for curriculum affairs, and Grade VIII students. Data were analyzed using the Miles and Huberman interactive model, while data validity was ensured through source and technique triangulation The findings indicate that the implementation of Deep Learning reflected three essential dimensions: meaningful learning, mindful learning, and joyful learning. The approach enhanced students' understanding of Pancasila values, promoted critical thinking skills, increased classroom participation, and encouraged students to connect learning materials with real-life experiences.